Students’ and Teacher’s Perceptions towards the Implementation of ProWritingAid and Teacher Feedback - Meilisa Sindy Astika Ariyanto; Nur Mukminatien; Sintha Tresnadewi (Graduate School of Universitas Negeri Malang, 2019)
Abstract: This study investigated the students’ and teacher’s perception, as well as, the merits and demerits of implementing ProWritingAid and teacher feedback in class. The design of this study was a survey research directed in an exclusive classroom setting. Based on the data analysis, it was found that both teacher and students perceived the strategy positively as it can help the students detect, learn, and fix their errors through ProWritingAid and revise their content through teacher feedback. It also helped the teacher in saving time and reduce the teacher’s workload.Abstrak: Penelitian ini menyelidiki persepsi siswa dan guru dalam penerapan metode pemberian umpan balik dari ProWritingAid dan guru di kelas. Metode yang digunakan dalam penelitian ini adalah survei yang diarahkan pada satu kelas terntentu. Berdasarkan analisis data yang dikumpulkan, ditemukan bahwa baik guru dan siswa memiliki pandangan positif terhadap strategi yang digunakan. Penggunaan strategu dirasakan positif karena dapat membantu siswa mendeteksi, belajar, dan memperbaiki kesalahan mereka melalui ProWritingAid dan memperbaiki isi paragraf mereka melalui umpan balik guru. Strategi ini juga membantu menghemat waktu dan mengurangi beban kerja guru.